Sensitivity Of Blood Cells Maturation Pattern In The Diagnosis Of Myelodysplastic Syndrome Using Flowcytometry - A Systematic Review - Nur Jihan Sinin; Ainoon Othman; Halimah Mustafa; Asral Wirda Ahmad Asnawi; Nazefah Abdul Hamid; Noor Fadzilah Zulkifli (Universiti Pendidikan Sultan Idris, 2024)
Clinical history, morphological appearance and cytogenetic data are required in identifying cases of MyelodysplasticSyndrome (MDS). However, this clonal stem cell disorder is still widely heterogenous and multiple tools are utilized in determining the diagnosis and prognosis. The current approaches in diagnosis are inherently subjective and lack of sensitivity. Over the years, altered maturation patterns using flow cytometry analysis have been reported to be useful for identification of MDS. This systematic review aims to assess the sensitivity of maturation pattern in obtaining MDS diagnosis. Electronic databases (MEDLINE, PROQUEST, OVID, Scopus, Web of Science) searched were yielded 677 articles. Snowballing was also employed. Two reviewers assessed each article independently using the following inclusion criteria: all types of MDS; WHO or FAB classification; diagnosis; immunophenotyping. Nineteen papers that met our inclusion criteria were analysed on the maturation pattern using flow cytometry. Samples used were bone marrow aspiration and prepared using either whole blood lysis or Ficoll-density gradient centrifugation. The most studied lineage in diagnosing MDS using maturation pattern is myeloid mainly looking on the CD34+, CD11b/CD16, CD13/CD16 and CD235a/CD71 expression pattern. Five studies showed sensitivity between 70 to 98 percent. Maturation pattern has shown high sensitivity and may be used as an ancillary technique for the diagnosis of MDS. However, flow cytometry strategies employed lack of standardization in assay, scoring system, and on how flow cytometry data have been analysed. Thus, more study need to be done within laboratory and multi-centre study to ensure validity and reliability of maturation pattern as an adjunct test.